Training volume and body composition as risk factors for developing jumper's knee among young elite volleyball players - Visnes, H.; Bahr, R. (Scandinavian Journal of Medicine & Science in Sports, 2013)
Training volume and body composition have been suggested as risk factors for jumper's knee among athletic youth, but research is lacking. The aim of this 4-year prospective cohort study was to examine the relationship between training and competition load, body composition, and risk for developing jumper's knee. Participants are elite volleyball players, aged 16-18 years. Training and competition load was recorded continuously and body composition semiannually. Jumper's knee was diagnosed on a standardized clinical examination. We recruited 141 healthy students (69 males and 72 females), and 28 developed jumper's knee (22 boys and six girls). In a multivariate analyses, boys had three to four times higher risk compared with girls. Volleyball training had an odds ratio (OR) 1.72 (1.18-2.53) for every extra hour trained, and match exposure was the strongest sports-related predictor for developing jumper's knee with an OR of 3.88 (1.80-8.40) for every extra set played per week. We did not detect any significant differences between the groups in body composition at the time of inclusion or in the change of body composition during the study period. Conclusion, male gender, a high volume of volleyball training and match exposure were risk factors for developing jumper's knee.